2012
DOI: 10.1063/1.4754122
|View full text |Cite
|
Sign up to set email alerts
|

In situ control of As dimer orientation on Ge(100) surfaces

Abstract: Direct observation of anti-phase boundaries in heteroepitaxy of GaSb thin films grown on Si(001) by transmission electron microscopy J. Appl. Phys. 112, 074306 (2012) Scaling behavior of GaAs and GaMnAs quantum rings grown by droplet epitaxy Appl. Phys. Lett. 101, 141901 (2012) Magnetron-sputter deposition of high-indium-content n-AlInN thin film on p-Si(001) substrate for photovoltaic applications J. Appl. Phys. 112, 063114 (2012) Growth mechanisms of ZnO(0001) investigated using the first-principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…1) largely overlaps with the RA spectrum of the clean UHV-prepared Ge(100) surface. The difference in RAS amplitude might be due to the coexistence of domains with mutually perpendicular orientation 5,31,32 or to a better surface cleanliness of the sample prepared in MOVPE ambient, since many studies report on the inevitable presence of C on UHV-prepared Ge(100) surfaces. 8,33,34 The clean and the monohydride-terminated Ge(100) surfaces exhibit characteristic RAS signals, which we will apply to study the hydrogen surface coverage during preparation in the process gas ambient of a MOVPE reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) largely overlaps with the RA spectrum of the clean UHV-prepared Ge(100) surface. The difference in RAS amplitude might be due to the coexistence of domains with mutually perpendicular orientation 5,31,32 or to a better surface cleanliness of the sample prepared in MOVPE ambient, since many studies report on the inevitable presence of C on UHV-prepared Ge(100) surfaces. 8,33,34 The clean and the monohydride-terminated Ge(100) surfaces exhibit characteristic RAS signals, which we will apply to study the hydrogen surface coverage during preparation in the process gas ambient of a MOVPE reactor.…”
mentioning
confidence: 99%
“…In the last years, there has been a renewed interest in the characterization of the structural and chemical properties of germanium (100) substrates for applications in microelectronics, 1 nanotechnology, 2 and photovoltaics. [3][4][5][6] A suitable surface preparation (in terms of surface cleanliness, termination, and reconstruction) is crucial for subsequent material and device properties. 7,8 In technologically relevant process ambients, the carrier gas (such as H 2 ) might affect surface reconstruction, 6,9 step formation, 10 and epitaxial growth.…”
mentioning
confidence: 99%
“…n-type and p-type carrier concentrations from 10 16 to 10 18 /cm 3 were differentiated based on the ability of RAS to measure the surface electric field resulting from the linear electro-optic effect associated with E 1 to E 1 þ D 1 transitions (near 3 eV) with respect to a reference undoped sample. Recent work by Bruckner et al [44] showed that key details associated with As adsorption and termination of Ge, such as dimer orientation, as well as the surface step structure can be differentiated using RAS by careful experiments and complementary STM, XPS, and low-energy electron diffraction (LEED) characterization, as shown in Figure 29.18. Relating the signal to surface coverage, RAS has also been used to monitor dopant (As) segregation during Si growth [43].…”
Section: Reflectance Anisotropy Spectroscopymentioning
confidence: 99%
“…Laterally patterned Si was used as a substrate to grow GaP with layers of alternating orientations as a result of differences in the GaP sublattice occupancy from antiphase domain differences created at steps. [44]. For comparison, the flipped and scaled (factor 1.38) RA spectrum of Ge (100):As 6 with predominant (2 Â 1) reconstruction is also depicted.…”
Section: Reflectance Anisotropy Spectroscopymentioning
confidence: 99%
“…While there have been many RAS studies of Si(001) surfaces, there have been very few studies of Ge(001), with recent work focusing on in situ MOVPE studies, where RAS has unique advantages. [8][9][10][11] Regarding calculations of the spectral response, the situation is similar. Recently, we have calculated the optical response of some Si(001) and Ge(001) surfaces using a local-orbital-based hybrid density functional theory (DFT) approach.…”
mentioning
confidence: 91%